Indian Journal of Nutrition and Dietetics - Sri Avinashilingam Home Science College for Women; Sri Avinashilingam Home Science College (Coimbatore, Sri Avinashilingam Home Science College for Women [etc.], 1970)
pRINT ONLY.
Keywords: Nutrition -- Periodicals; Dietetics -- Periodicals; Nutrition -- Periodicals; Nutrition -- Périodiques.